Tracking in Nature's Footsteps: The Intersection of Environmental Education and Philosophy - Dakkal Harahap; Tobroni , Tobroni; Widodo, Joko (Assyfa Journal of Multidisciplinary Education, 2023)
The ecological crisis has hit parts of the world due to the imbalance in the relationship between humans and nature, so it is very important and urgent to have a practical and scientific understanding of environmental education with ethical and conceptual reflections from philosophy. This research aims to answer the research question, "How can the intersection between environmental education and philosophy foster deeper environmental awareness in society?" This study uses a systematic literature review (SLR) methodology, with the PRISMA technique to analyze various literature sources including books, journal articles, and reviews. Data were collected from publications in the Scopus database from April 2011 to May 2023, using keywords such as "Intersection", "Education", "Environmental", "Science", and "Philosophy". Bibliometric analysis using VOSviewer revealed several specific findings, including an increasing trend of research integrating environmental education and philosophy, as well as the identification of key concepts linking the two fields. These findings highlight the important role of combining environmental education and philosophy in fostering a society that is environmentally conscious, full of ethics, and respects sustainability. By integrating environmental philosophy into the education curriculum, we can grow generations who are more responsible, and wise in preserving the environment. This study provides valuable insights for policymakers, educators, and stakeholders committed to promoting sustainable environmental management and offers practical recommendations for its implementation in education.